Kajian tentang Belajar dalam al-Qur'an Surat al-'Alaq Ayat 1-5 - A. Syafi' AS. (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2017)
This study aims to examine the learning contained in the Qur'an Surah al-'Alaq verses 1-5, because these verses are loaded with information about the importance of learning. In addition, in the Qur'an there are many verses that explain the basics of learning in the sense of exploring knowledge and developing it for the welfare and virtue of man in his life. Sources of data that the authors use is al-Qur'an Surah al-'Alaq verses 1-5 and other verses about learning and tafsirnya. The data collection in this research is done through literature study. While the data analysis using tahlily method, according to Baqir al-Shadr as tajzi'iy method, and content analysis method is a technique to draw conclusions by identifying the specific characteristics of a message subjectively and systematically. The results of this study indicate that learning in Surah al-'Alaq verses 1-5 is the ultimate command of Allah to Muslims by means of the word Iqra (read), reading here does not mean just reading a text only, but reading nature, the circumstances around us. Surah al-'Alaq uses the word iqra' and qalam, both of which are of vital importance in the process of learning and/or exploring knowledge.